2012
DOI: 10.3928/1081597x-20121005-04
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Topography-based Customized Ablations for Myopia and Myopic Astigmatism

Abstract: PURPOSE: To evaluate clinical outcomes after primary treatments for myopia and myopic astigmatism with topography-based ablation profiles on the Allegretto Wave Eye-Q platform (Alcon Laboratories Inc). METHODS: Records of patients who underwent topography-guided, Q-adjusted LASIK were retrieved and analyzed. Patients with mean refractive spherical equivalent up to −16.00 diopters (D) and cylindrical errors up to 6.00 D were included (2051 eyes). Refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…There is some evidence that the use of iris registration may improve refractive outcomes in some cases . Numerous studies have examined the efficacy of laser refractive surgery procedures, and results with modern LASIK and PRK platforms generally demonstrate predictable correction of low to moderate astigmatic refractive errors (up to ~3 DC), particularly for myopic astigmatism, with recent studies reporting average post‐surgical levels of residual refractive astigmatism from 0.11 to 0.68 DC . Although refractive stabilisation and visual recovery is generally faster with LASIK compared to PRK, studies comparing the two procedures have generally found the refractive and visual outcomes in the long term to be similar for the two procedures using modern techniques for patients with low to moderate myopic astigmatism …”
Section: The Clinical Correction Of Astigmatismmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that the use of iris registration may improve refractive outcomes in some cases . Numerous studies have examined the efficacy of laser refractive surgery procedures, and results with modern LASIK and PRK platforms generally demonstrate predictable correction of low to moderate astigmatic refractive errors (up to ~3 DC), particularly for myopic astigmatism, with recent studies reporting average post‐surgical levels of residual refractive astigmatism from 0.11 to 0.68 DC . Although refractive stabilisation and visual recovery is generally faster with LASIK compared to PRK, studies comparing the two procedures have generally found the refractive and visual outcomes in the long term to be similar for the two procedures using modern techniques for patients with low to moderate myopic astigmatism …”
Section: The Clinical Correction Of Astigmatismmentioning
confidence: 99%
“…272,273 Numerous studies have examined the efficacy of laser refractive surgery procedures, and results with modern LASIK and PRK platforms generally demonstrate predictable correction of low to moderate astigmatic refractive errors (up to~3 DC), particularly for myopic astigmatism, 274 with recent studies reporting average post-surgical levels of residual refractive astigmatism from 0.11 to 0.68 DC. [275][276][277][278][279][280] Although refractive stabilisation and visual recovery is generally faster with LASIK compared to PRK, studies comparing the two procedures have generally found the refractive and visual outcomes in the long term to be similar for the two procedures using modern techniques for patients with low to moderate myopic astigmatism. 274 It is well established that although conventional corneal refractive surgery procedures effectively correct spherocylindrical refractive errors, they can result in an increase in the eye's higher-order aberrations, particularly spherical aberration.…”
Section: Cataract Surgerymentioning
confidence: 99%
“…Topography does not provide spherical power, as eye length is not measured. Tan et al1 presented a large set of 2051 primary eyes, corrected with topography-guided ablation specifically only using the manifest refraction. In a US FDA study, Stulting et al2 also only used the manifest refraction, but the FDA approval did not specify whether manifest or Contoura measured refraction was to be used.…”
Section: Introductionmentioning
confidence: 99%
“…Residual astigmatism less than 0.50D has an impact on 3 visual quality [5] . With the development of technology, wavefront-guided [6][7] and topographyguided [8][9] had been used in LASIK. The conventional treatment method is wavefront-guided LASIK, which aims to correct the aberration of the entire eye and is gradually less effective with age due to changes in eye adjustment [6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Topography-guided LASIK have been reported to correct irregular cornea. It has showed advantages for improved visual quality with less induction of high order aberrations (HOAs) [8][9] . In recent years, Alcon presented the innovative Contoura Vision technique based on the WaveLight refractive Suite.…”
Section: Introductionmentioning
confidence: 99%